A produção científica em direitos humanos nos países do sul global: uma análise bibliométrica e cientométrica da Sur Revista Internacional de Direitos Humanos - Ana Claudia Ribeiro (2016)
The following work aims the analysis of scientific production on Human Rights by the Global South, through a study of the authors and the content of the publications of the International Journal of Human Rights. As a research schedule, it were adopted the methodologies of bibliometric and scientometric analysis, which grant mechanisms to become able to make a frame of the scientific background production of the Journal. The first stage of the analysis focuses on understanding the sociopolitical context of the authors, regarding these variables: level of academic qualification, area of academic qualification, institutional affiliation, birth origin and place of institutional affiliation. Despite the preponderance of Law Science on authors professional practice, it gets prominent, with the results of the research, the contribution of authors belonging to others knowledge areas such as Sociology, International Relations, Political Science, Philosophy, among others, confirming the interdisciplinary bonds in the domain of Human Rights. Institutional affiliation indicates a high level of participation of authors belonging to universities and NGOs, what shows that those institutions influence the Global Agenda for human rights and impel their members to write under the bias of the Agenda. Another substantial finding is the expressive participation of authors coming from Europe and the United States, signaling an influence of the Northern Hemisphere on the scientific production of the South. The analysis of content was made by indexing the articles, following the standardization of the Thesaurus of the Inter-American Court, adapted by the researcher according to the literature on the area. Due to this change, it becomes evident the need to rethink the controlled vocabulary systems of the area, in order to contemplate terms related to contemporary matters. The results of the analysis on these subjects show that the most debated topic deals with issues related to the Third Dimension Rights, characterized by Collective Transindividual Rights as refugee groups, women, children, LGBTI, handicapped, ethnic and indigenous peoples. The second most important issue belongs to the Second Dimension of Rights, and deal with matters such as judicialization of rights - related to the effectiveness of international jurisdiction and internationalization of Human Rights. It were also revealed subjects that are less prominent in the Journal, such as the Right to Development and the Environment Rights. This is a problematic point of the Journal, because such themes are the core of the new Global Agenda, which are under wide discussion in the UN climate forums.